1994
DOI: 10.1177/107110079401500804
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy of the Subtalar Joint

Abstract: The purpose of this study was to determine the position and relative safety of the anterior, posterior, and newly defined middle portals by measuring their distance from the neurovascular structures and tendons on the lateral side of the foot and ankle. Furthermore, this study demonstrates specific components of the posterior subtalar joint and arthroscopic access to each utilizing a technique that allows direct anatomic correlation. The 15 specimens were divided into three groups of five feet each, with one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 12 publications
1
44
1
3
Order By: Relevance
“…In these studies, procedures were performed through either a posterior (posteromedial and posterolateral portals) or lateral (anterolateral and posterolateral portals) approach. One concern relating to these approaches is proximity of the posterolateral portal to the sural nerve, with a 10% incidence of nerve injury seen in cadaveric studies [26,27]. To avoid a posterolateral portal, and to access all three facets of the subtalar joint, we use a two-portal sinus tarsi approach that has previously been described in the literature [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, procedures were performed through either a posterior (posteromedial and posterolateral portals) or lateral (anterolateral and posterolateral portals) approach. One concern relating to these approaches is proximity of the posterolateral portal to the sural nerve, with a 10% incidence of nerve injury seen in cadaveric studies [26,27]. To avoid a posterolateral portal, and to access all three facets of the subtalar joint, we use a two-portal sinus tarsi approach that has previously been described in the literature [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…The ALV portal is just posterior to the anterior calcaneal process. Using this access, the dorsal cutaneous branch of the su- [7] perficial peroneal nerve, the dorsal lateral cutaneous nerve at the end of the sural nerve as well as the tendon of the peroneal tertial muscle and branches of the small saphenous vein have to be avoided. This can be managed by a superficial retrograde skin incision and a subcutaneous preparation down to the joint capsule, which is performed by a haemostat.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Frey et al [7] showed in anatomic studies that from these two portals 90% of the posterior joint facet can be reached. Only a small medial part is not accessible, but this area can be reached from the ALD portal (Fig.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…However, peritendinous portals placed adjacent to the Achilles tendon in the prone patient are safe. 4,12,[16][17][18][19][20] The purpose of the study was to report the clinical outcomes of arthroscopic excision for a symptomatic os trigonum initially viewing through the posteromedial ankle portal with the motorized instrument in the posterolateral portal. Our hypothesis was that this approach would be both safe and effective and would provide comparable outcomes, a comparable complication rate, and a comparable recovery to other arthroscopic techniques.…”
mentioning
confidence: 99%